Rotavirus A genotype diversity and antigenic profile in Central Ethiopia: implications for rotarix® vaccine efficacy - Redda, Yisehak Tsegaye; Adamu, Haileeyesus; Bergholm, Julia; Lindahl, Johanna F.; Blomström, Anne-Lie; Berg, Mikael; Sisay Tessema, Tesfaye (Frontiers in Microbiology, 2025)
IntroductionRotavirus remains a leading cause of severe gastroenteritis in children globally, including in Ethiopia. Despite the introduction of vaccines, high mutation and reassortment rates contribute to genetic diversity and potential vaccine escape. This study aimed to assess the distribution and genetic characteristics of rotavirus A (RVA) strains in children under five with diarrhea in central Ethiopia, with comparison to the Rotarix® vaccine strain.MethodsStool samples were collected from children under 5 years of age presenting with diarrhea at health centers in Debre Berhan and Addis Ababa between April 2022 and December 2023. RVA was detected using quantitative real-time PCR (qPCR). Genotyping was performed by Sanger sequencing of the VP7 and VP4 genes. Phylogenetic analysis was performed in MEGA X software using the maximum likelihood method with 1,000 bootstrap replicates, using reference sequences retrieved from the GenBank database. Amino acid sequences of these proteins were compared with those of the Rotarix® vaccine strain to identify substitutions in key antigenic regions.ResultsRVA was detected in 30 of 247 samples (12.14%), with 28 successfully genotyped. G9 was the predominant G genotype (50%), followed by G12 (10.2%), G2 (7.1%), G1 (3.6%), and G3 (3.6%); 25% remained untyped. P[4] was the most common P genotype (28.6%), followed by P[6] (21.4%) and P[8] (17.9%), with 32.1% untyped. The most frequent G/P combinations were G9P[4] (35%), G12P[6] (13%), and G9P[8] (9%). Compared to Rotarix®, the circulating G2, G3, G9, and G12 strains showed 18, 12, 13, and 17 amino acid substitutions, respectively, within the 29-residue VP7 epitopes. The P[8], P[4], and P[6] strains exhibited 4, 9, and 18 substitutions, respectively, within the 28 VP4 neutralizing epitope residues. Phylogenetic analysis revealed that the current identified virus mainly clusters with strains previously reported from Ethiopia, indicating a shared evolutionary origin.ConclusionThe dominance of the G9P[4] genotype, together with substantial amino acid substitutions in the current circulating RVA strains that diverge from the G1P[8] Rotarix® strain, may compromise vaccine performance. These findings underscore the need to evaluate vaccine efficacy, maintain molecular surveillance, and incorporate broader genotype coverage in future vaccine design.